The POTENTIAL OF UTILIZING THE MONUMEN PAHLAWAN PANCASILA AS A COLLECTIVE MEMORY OF THE EVENTS OF THE 30 SEPTEMBER 1965 MOVEMENT IN KENTUNGAN YOGYAKARTA - Mona Riza Nuragnianti; Komang Ayu Suwindiatrini; Anggrita Salfa Pharmacytha; Christoffer Erfrans Wantania (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
The events of the 30 September Movement or G30S are evidence of the dark history of the Indonesian people which occurred in Jakarta and Yogyakarta. Monumen Pahlawan Pancasila is evidence of the events of the 30 September Movement which was built in Kentungan, Yogyakarta. This research discusses the meaning of G30S from various stakeholders and also the potential use of the Monumen Pahlawan Pancasila in Kentungan, Yogyakarta. This research uses qualitative methods with stages of observation, in-depth interviews, document analysis in the form of collection archives, news and journals and uses purposive sampling techniques. The novelty of this article is a study related to the meaning of G30S and the potential use of the Monumen Pahlawan Pancasila as a Collective Memory.